Method for reusing positive electrode active material

Through polar solvent separation, heat treatment, removal of adhesives and conductive materials, alkaline washing and lithium precursor heating, the problem of recycling and reuse of active substances for positive electrodes of lithium-ion batteries is solved, and an acid-free, environmentally friendly and efficient reuse process is achieved.

JP7648797B2Active Publication Date: 2025-03-18LG ENERGY SOLUTION LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2023562582
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-26
Filing Date
2022-08-19
Publication Date
2025-03-18
Estimated Expiration
2042-08-19

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recover and reuse positive electrode active substances of lithium-ion batteries, especially in the removal of ceramic particles and other foreign substances, and traditional methods use acid dissolution to cause environmental pollution and high costs.

Method used

The positive electrode plate is separated by immersing the stacked battery in a polar solvent, and the adhesive and conductive material of the electrode plate are removed at high temperature to separate the live material layer and the current collector, and then the live material is washed with an alkaline lithium hydroxide solution, and the lithium precursor substance is added by heating to restore the reusable state of the live material.

Benefits of technology

The reuse of active substances of positive electrodes under the acid-free method is achieved, which avoids environmental pollution and high costs. The recovered live substances can be directly reused for lithium-ion battery manufacturing, maintaining good electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648797000008
    Figure 0007648797000008
  • Figure 0007648797000009
    Figure 0007648797000009
  • Figure 0007648797000010
    Figure 0007648797000010
Patent Text Reader

Abstract

A method for reusing a positive electrode active material according to the present invention includes the steps of: immersing a stack cell including a stacked and combined positive electrode plate, a separator, and a negative electrode plate in a polar solvent to separate the positive electrode plate; heat-treating the separated positive electrode plate to thermally decompose a binder and a conductive material in a positive electrode active material layer of the positive electrode plate, thereby separating a current collector of the positive electrode plate from the active material layer and recovering an active material in the active material layer; washing the recovered active material with an aqueous solution of a lithium compound that is basic in an aqueous solution state; and adding a lithium precursor to the washed active material and annealing it to obtain a reusable active material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for recycling resources during the manufacture of lithium secondary batteries. In particular, the present invention relates to a method for recovering and reusing a positive electrode active material from a defective stack cell generated in the manufacturing process of a lithium secondary battery or a lithium secondary battery that is discarded after use. This application claims priority based on Korean Patent Application No. 10-2021-0113482 filed on August 26, 2021, and the contents disclosed in the specification and drawings of the application are incorporated herein in their entirety. [Background technology]

[0002] Lithium secondary batteries, which can be repeatedly charged and discharged, have been attracting attention as an alternative to fossil energy. Lithium secondary batteries have been mainly used in traditional handheld devices such as mobile phones, video cameras, and power tools. However, in recent years, their application has gradually expanded to include electrically powered automobiles (electric vehicles (EVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs)), large-capacity energy storage systems (ESSs), and uninterruptible power supplies (UPSs).

[0003] A lithium secondary battery includes an electrode assembly in which unit cells are assembled, each having a structure in which a positive electrode plate and a negative electrode plate, each having an active material coated on a current collector, are arranged with a separator between them, and an exterior material, for example, a battery case, that seals and houses the electrode assembly together with an electrolyte. A lithium-based oxide is mainly used as the positive electrode active material of a lithium secondary battery, and a carbon material is used as the negative electrode active material. The lithium-based oxide contains metals such as cobalt, nickel, and manganese. In particular, cobalt, nickel, and manganese are very expensive valuable metals, and among them, cobalt belongs to the strategic metals, and countries around the world have a special interest in supply and demand. Since the number of cobalt producing countries is limited, it is known as a metal whose supply and demand is unstable worldwide. If an imbalance in supply and demand occurs for strategic metal raw materials, there is a high possibility that raw material prices will rise.

[0004] In the past, research has been conducted on recovering and recycling valuable metals from lithium secondary batteries (waste batteries) that are discarded after the end of their life. In most conventional methods for recovering positive electrode active materials, the positive electrode is dissolved with hydrochloric acid, sulfuric acid, nitric acid, etc., and active material elements such as cobalt, nickel, and manganese are extracted and used as raw materials for synthesizing positive electrode active materials again. However, the method of extracting active material elements using an acid has the disadvantages that the process for recovering pure raw materials is not environmentally friendly, and a neutralization process and a wastewater treatment process are required, which increases the process cost. In addition, it has the disadvantage that lithium, which is one of the main elements of the positive electrode active material, cannot be recovered. In order to solve these disadvantages, a method is needed that does not dissolve the positive electrode active material and does not extract the active material in the form of an element, but can directly reuse it.

[0005] Meanwhile, among the types of lithium secondary batteries, in the case of pouch-type batteries, stack cells are used in which a positive electrode plate, a separator, and a negative electrode plate are laminated and combined by heat pressing (so-called lamination). When a separator coated with ceramic particles such as inorganic compounds / inorganic oxides is used as the separator, the ceramic particles may be transferred to the positive electrode active material side of the positive electrode plate during heat pressing. In order to recover and reuse the positive electrode active material from defective stack cells generated in the manufacturing process of lithium secondary batteries or from deteriorated electrodes of lithium secondary batteries discarded after use, it is necessary to remove the ceramic particles transferred to the positive electrode active material. However, none of the previously proposed methods for recovering the positive electrode active material have presented a clear process for separating the positive electrode from the stack cell or deteriorated electrode, and furthermore, they do not consider the treatment of the ceramic particles transferred to the positive electrode active material. Summary of the Invention [Problem to be solved by the invention]

[0006] The problem to be solved by the present invention is to provide a method for recovering and reusing a positive electrode active material from a defective or deteriorated electrode of a stack cell. [Means for solving the problem]

[0007] In order to solve the above problems, a method for reusing a positive electrode active material according to the present invention includes the steps of: immersing a stack cell including a stacked and combined positive electrode plate, a separator, and a negative electrode plate in a polar solvent to separate the positive electrode plate; heat-treating the separated positive electrode plate to thermally decompose a binder and a conductive material in a positive electrode active material layer of the positive electrode plate, thereby separating a current collector of the positive electrode plate from the active material layer and recovering an active material in the active material layer; washing the recovered active material with an aqueous solution of a lithium compound that is basic in an aqueous solution state; and adding a lithium precursor to the washed active material and annealing it to obtain a reusable active material.

[0008] In the present invention, it is preferable to use acetone as the polar solvent.

[0009] The present invention may further include the step of applying a surface coating to the annealed active material.

[0010] In the present invention, the method may further include a step of coating the surface of the annealed active material after cleaning the active material.

[0011] The heat treatment may be carried out at 300 to 650° C. in air or an oxygen atmosphere.

[0012] The heat treatment may be carried out at 550° C. for 30 minutes with a temperature ramp rate of 5° C. / min.

[0013] The lithium compound aqueous solution is prepared to contain more than 0% to 15% of the lithium compound, and preferably uses LiOH. The washing can be performed by immersing the recovered active material in the lithium compound aqueous solution while stirring it.

[0014] The lithium precursor may be any one or more of LiOH, Li2CO3, LiNO3, and Li2O.

[0015] The lithium precursor may be added in an amount that corresponds to the ratio of lost lithium relative to the ratio of lithium and other metals in the raw active material used in the active material layer.

[0016] For example, the lithium precursor may be added such that lithium is added in an amount between 0.001 and 0.4 molar ratio.

[0017] Furthermore, preferably, the lithium precursor may be added so that lithium is further added in an amount of 0.0001 to 0.1 molar ratio based on a molar ratio of lithium to other metal of 1:1.

[0018] The annealing may be carried out at 400 to 1000° C. in air or an oxygen atmosphere.

[0019] The temperature of the annealing step may be above the melting point of the lithium precursor.

[0020] The active material in the active material layer is recovered in a powder form, and carbon components resulting from carbonization of the binder and conductive material may not remain on the surface.

[0021] In the surface coating step, at least one of a metal, an organometallic component, and a carbon component may be coated on the surface in a solid or liquid phase manner, and then heat-treated at 100 to 1200°C.

[0022] In the present invention, the positive electrode active material is a lithium transition metal composite oxide containing nickel, cobalt, and manganese or aluminum, and the content of the nickel may be 60 mol % or more based on the total number of moles of the transition metals.

[0023] The reusable active material may have a fluorine (F) content of 100 ppm or less.

[0024] After the washing step, the method may further include mixing the washed active material with a lithium precursor solution and spray drying. Effect of the Invention

[0025] According to the present invention, the positive electrode active material can be reused without using an acid, which is environmentally friendly. The method according to the present invention does not require a neutralization process or a wastewater treatment process, which alleviates environmental issues and reduces process costs.

[0026] According to the present invention, the positive electrode active material can be recovered without metal elements that cannot be recovered. The current collector can also be recovered because it is not dissolved. Instead of extracting the active material elements and using them again as raw materials for synthesizing the positive electrode active material, the recovered active material in powder form can be directly reused, which is economical.

[0027] According to the present invention, since no toxic and explosive solvents such as N-methyl-2-pyrrolidone (NMP), dimethyl carbonate (DMC), or methanol are used, the present invention is safe, and since simple processes such as heat treatment, cleaning, and annealing are adopted, the process control is easy and the present invention is suitable for mass production.

[0028] According to the present invention, excellent resistive and capacitive properties can be achieved without deteriorating the electrochemical performance of the recovered active material.

[0029] In particular, according to the present invention, there is an advantage that reused active material can be obtained without the occurrence of defective stack cells that occur during the lithium secondary battery manufacturing process or the inclusion of foreign matter such as ceramic particles from a separator in a deteriorated electrode.

[0030] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to facilitate a further understanding of the technical ideas of the present invention as well as the content of the invention, and therefore the present invention should not be interpreted as being limited to only the matters depicted in the drawings. [Brief description of the drawings]

[0031] [Figure 1] 2 is a flow chart of a method for reusing active materials according to one embodiment of the present invention. [Diagram 2] 4 is a flowchart of a method for reusing active materials according to another embodiment of the present invention. [Diagram 3] 10 is a flowchart of a method for reusing active materials according to yet another embodiment of the present invention. [Figure 4a] This is a photo of a stack cell. [Figure 4b] 1 is a photograph of a positive electrode plate before forming a stack cell. [Figure 4c] 1 is a photograph of a positive electrode plate in a state where the negative electrode plate and the separator are only physically separated after the stack cell is formed. [Figure 4d] 1 is a photograph of a positive electrode plate in a state where the negative electrode plate and the separator are only physically separated after the stack cell is formed. [Diagram 5] FIG. 4c is a photograph of the active material recovered after heat treatment of the positive plate. [Figure 6] This is a photograph of the positive electrode plate in Figure 4c after it was immersed in acetone for a certain period of time. [Figure 7a] 1 is a photograph of a stack cell immersed in acetone. [Figure 7b] This is a photograph of the positive electrode plate being lifted from the stack cell after a predetermined time has elapsed. [Figure 7c] 1 is a photograph of a positive plate completely separated from a stack cell. [Figure 8] 1 shows the results of cell evaluation carried out using the active materials of the examples and the comparative examples for the NCM-based active material. [Figure 9] 1 shows the results of cell evaluation carried out on an LCO active material using active materials of an example and a comparative example. [Figure 10] 13 shows the results of cell evaluation carried out using other LCO active materials, including active materials of examples and comparative examples. [Figure 11] 1 shows X-ray diffraction (XRD: X-Ray Diffraction) patterns of active materials of Examples and Comparative Examples. [Figure 12]1 is a scanning electron microscope (SEM) photograph of active materials of examples and comparative examples. [Figure 13] 1 is a particle size distribution graph of active materials of Examples and Comparative Examples. [Figure 14] 13 shows the results of cell evaluation carried out using other NCM-based active materials, including active materials of Examples and Comparative Examples. [Figure 15] 13 shows the results of cell evaluation carried out using other NCM-based active materials, including active materials of Examples and Comparative Examples. [Figure 16] 1 shows the results of cell evaluation of high Ni content NCM-based active materials using active materials of Examples and Comparative Examples. [Figure 17] 1 shows the results of cell evaluation of high Ni content NCM-based active materials using active materials of Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the attached drawings. Prior to this, the terms and words used in this specification and claims are not to be construed as being limited to their ordinary or dictionary meanings, but are to be construed as being in accordance with the meaning and concept of the technical idea of ​​the present invention, in accordance with the principle that the inventor himself can appropriately define the concept of the term in order to best describe the invention. Therefore, it should be understood that the embodiment described in this specification and the configuration shown in the drawings are merely the most preferred embodiment of the present invention, and do not represent the entire technical idea of ​​the present invention, and therefore there may be various equivalents and modifications that can be substituted therefor at the time of this application.

[0033] In the following description, reference is made to the accompanying drawings, which form a part hereof. The implementations described in the detailed description, the drawings, and the claims are not intended to be limiting. Other embodiments may be utilized, and other changes may be made, without departing from the spirit and scope of the subject matter disclosed herein. It will be readily understood that the aspects of the invention as generally described herein and illustrated in the drawings can be arranged, substituted, combined, separated, and designed in a variety of different configurations, all of which are expressly contemplated herein.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs.

[0035] The present invention is not limited with respect to the specific embodiments described herein. As will be apparent to those skilled in the art, many changes and modifications can be made without departing from the spirit and scope of the present invention. In addition to those enumerated herein, functionally equivalent methods within the scope of the present invention will be apparent to those skilled in the art from the foregoing description. Such changes and modifications are within the scope of the appended claims. The present invention is limited only by the claims, along with the full scope of equivalents defined by such claims. It is to be understood, of course, that the present invention is not limited to the specific ways in which it can be modified. It is also to be understood that the terminology used herein is for the purpose of describing specific embodiments only, and is not intended to be limiting.

[0036] Conventional active material recycling processes mainly involve extracting valuable metals (nickel, cobalt, manganese, etc.) as elements from lithium secondary battery active materials whose performance has deteriorated after use, and resynthesizing the active materials. In contrast, the present invention is differentiated in that it recovers active materials from defective stack cells or deteriorated electrodes including stack cells that occur during the lithium secondary battery manufacturing process.

[0037] In addition, in the case of the conventional active material recycling process, valuable metals are extracted by acid / base dissolution or reduction / melting with additives, and then chemical methods such as manufacturing the metals (direct reduction method) or resynthesized active materials are added, which increases the process complexity and economic costs. However, the present invention relates to a method for directly reusing the positive electrode active material without dissolving it.

[0038] To directly reuse the positive electrode active material, a method is required to remove the current collector from the positive electrode, which can be achieved by high-temperature heat treatment to remove the binder, by using a solvent to dissolve the binder, by completely dissolving the current collector, or by dry grinding and sieving to separate the active material.

[0039] When using a solvent to dissolve the binder, the stability of the solvent is important. NMP is the most efficient solvent, but it has the disadvantages of toxicity and high cost. Another disadvantage is that a solvent recovery process, such as reprocessing the waste solvent, is required. Dissolving the current collector can be less costly than using a solvent. However, it is difficult to remove foreign matter from the surface of the reused active material, and hydrogen gas is generated during the current collector removal process, which may cause an explosion. It is difficult to completely separate the current collector from the active material by dry grinding and sieving. The particle size distribution of the active material changes during the grinding process, making it difficult to remove the binder, which has the disadvantage of deteriorating the battery characteristics when it is reused.

[0040] In the present invention, the active material and the current collector are separated using a high-temperature heat treatment. The high-temperature heat treatment is advantageous for mass production and commercialization. However, foreign matter must not remain on the surface of the reused active material. In the present invention, a step of removing foreign matter from the surface of the reused active material is also proposed.

[0041] In particular, when recycling a positive electrode active material from a stack cell, it is important to prevent foreign matter from the separation membrane from being mixed into the positive electrode active material. In the present invention, a separation membrane coated with ceramic particles such as inorganic compounds / inorganic oxides is used as the separation membrane, and a method is proposed for recycling the positive electrode active material by completely separating the positive electrode plate so that the ceramic particles are not mixed into the positive electrode active material even if the ceramic particles are transferred to the positive electrode active material side.

[0042] Hereinafter, a method for reusing an active material according to an embodiment of the present invention will be described with reference to FIGS.

[0043] First, the method of FIG. 1 is suitable for the case where the positive electrode active material is a lithium cobalt oxide such as LiCoO2 (LCO).

[0044] Referring to FIG. 1, a stack cell including a stacked and combined positive electrode plate, separator, and negative electrode plate is immersed in a polar solvent to separate the positive electrode plate (step S10).

[0045] The positive electrode plate may be punched out from a positive electrode sheet including a positive electrode active material layer formed on a positive electrode current collector such as aluminum foil. The negative electrode plate may also be punched out from a negative electrode sheet including a negative electrode active material layer formed on a negative electrode current collector such as copper foil. The separator may be a polymer substrate coated with ceramic particles such as inorganic compounds / inorganic oxides. When coating the separator with ceramic particles, a coating liquid is used that is prepared by adding a binder, ceramic particles, and a dispersant to a highly volatile solvent in order to coat the separator with ceramic particles thinly and quickly.

[0046] The stack cells are assembled by hot pressing (so-called lamination), and when a separator coated with ceramic particles such as inorganic compounds / inorganic oxides is used as a separator, the ceramic particles may be transferred to the positive electrode active material side of the positive electrode plate during hot pressing. Step S10 proposed by the present invention is very suitable for separating the positive electrode plate while removing the ceramic particles transferred to the positive electrode active material.

[0047] The polar solvent in step S10 is preferably the same as the solvent used to manufacture the separation membrane. When the stack cell is immersed in such a solvent, the ceramic particles fall off into the solvent. Preferably, the polar solvent is acetone. When the stack cell is immersed in acetone, the positive electrode plate, the negative electrode plate, and the separation membrane, which are components of the stack cell, are easily separated, and the ceramic particles transferred to the positive electrode active material during the heat-pressing of the separation membrane can be separated from the positive electrode plate.

[0048] It has been experimentally confirmed that when the positive electrode plate is only physically separated from the stack cell without immersion in a polar solvent as in step S10 and the subsequent steps are performed, the ratio of ceramic particles included increases. It has also been confirmed that the capacity expression rate decreases when a recycled active material is obtained while still containing ceramic particles. Therefore, a step such as step S10 of the method proposed by the present invention is necessary to increase the capacity expression rate.

[0049] Next, the separated positive electrode plate is crushed to an appropriate size (step S20). Crushing refers to cutting or shredding the positive electrode plate to an appropriate size that is easy to handle. After crushing, the positive electrode plate is cut into small pieces, for example, 1 cm x 1 cm. For crushing, various dry crushing devices such as a hand mill, a pin mill, a disk mill, a cut mill, and a hammer mill may be used, or a high-speed cutter may be used.

[0050] The crushing may be performed taking into consideration the handling of the positive plate and the required characteristics of the equipment used in the subsequent process. For example, when using equipment that requires continuous processing in loading and unloading the positive plate, the positive plate must have good fluidity, so positive plates that are too large must be crushed. If the positive plate is of an appropriate size, the crushing step S20 can be omitted.

[0051] Next, the positive electrode plate is heat-treated (step S30).

[0052] The active material layer is formed by coating a slurry that is a mixture of an active material, a conductive material, a binder, a solvent, etc., and has a structure in which the active material and the conductive material are bound by the binder after the solvent evaporates. Therefore, the present invention was completed by focusing on the fact that the active material can be separated from the current collector by removing the binder.

[0053] In the present invention, the heat treatment is performed to thermally decompose the binder in the active material layer. The heat treatment in step S30 can be performed at 300 to 650°C, and can be called a high-temperature heat treatment. At temperatures below 300°C, it becomes difficult to remove the binder, and a problem occurs in which the current collector cannot be separated, while at temperatures above 650°C, the current collector melts (Al melting point: 660°C), and a phenomenon occurs in which the current collector cannot be separated.

[0054] The heat treatment time is maintained to a degree that the binder can be sufficiently thermally decomposed. For example, it is about 30 minutes. It is preferably 30 minutes or more. The longer the heat treatment time, the longer the time for the binder to thermally decompose, but once it reaches a certain time, there is no difference in the effectiveness of the thermal decomposition. Preferably, the heat treatment time is 30 minutes or more and 5 hours or less.

[0055] The heat treatment device can be a furnace of various forms, for example, a box furnace or, considering productivity, a rotary kiln capable of continuous treatment.

[0056] After the heat treatment, the material may be cooled slowly or rapidly in air.

[0057] For example, the heat treatment can be performed at 550°C for 30 minutes with a temperature rise rate of 5°C / min. The temperature rise rate is, for example, a rate that can be reasonably achieved in a box furnace and that can heat the positive plate without causing thermal shock. 550°C takes into consideration the melting point of the Al current collector and allows the binder to easily decompose. At this temperature, heat treatment for less than 10 minutes will not result in sufficient decomposition, so heat treatment must be performed for 10 minutes or more, and preferably for 30 minutes or more.

[0058] By the heat treatment in air, the binder and conductive material in the active material layer are thermally decomposed, becoming CO2 and H2O, which are then removed. By removing the binder, the active material is separated from the current collector, and the active material to be recovered can be selected in powder form. Therefore, the current collector can be separated from the active material layer and the active material in the active material layer can be recovered in just step S30.

[0059] It is important that the heat treatment in step S30 is carried out in air. If the heat treatment is carried out in a reducing gas or inert gas atmosphere, the binder and conductive material will not be thermally decomposed and only carbonization will proceed. If only carbonization proceeds, the carbon components will remain on the surface of the active material, reducing the performance of the reused active material. If the heat treatment is carried out in air, the carbon substances in the binder and conductive material will react with oxygen and be burned and removed with CO and CO2 gas, so that the binder and conductive material are almost completely removed with no residue remaining.

[0060] Therefore, according to the present invention, the active material is recovered in a powder form, and carbon components generated by carbonization of the binder or conductive material do not remain on the surface.

[0061] Next, the recovered active material is washed (step S40). When washing, it is important to wash with an aqueous solution of a lithium compound that is alkaline in an aqueous solution state. Such an aqueous solution of a lithium compound is prepared to contain more than 0% and not more than 15% of a lithium compound, and preferably LiOH is used. The amount of LiOH is preferably 15% or less. The use of excess LiOH may cause excess LiOH to remain on the surface of the active material even after washing, which may affect the subsequent annealing process. As much as possible, in order to clean the surface of the active material in a step before annealing, the addition of excess LiOH is not preferable in the process, so it is limited to 15% or less.

[0062] The washing can be performed by immersing the recovered active material in such an aqueous lithium compound solution. The washing can be performed within one week, preferably within one day, and more preferably within one hour after the immersion. If the washing is performed for more than one week, lithium may be excessively dissolved, resulting in a decrease in capacity. Therefore, it is desirable to perform the washing within one hour. The washing includes immersing the active material in an aqueous lithium compound solution that is basic in the aqueous solution state, stirring the solution while the active material is immersed, and the like. It is preferable to use stirring as much as possible. If the active material is simply immersed in the aqueous lithium compound solution without stirring, the washing process will be slow, which may cause lithium to dissolve. If stirring is used in combination, the process time can be minimized, so it is preferable to stir the active material simultaneously with the impregnation with the aqueous lithium compound solution.

[0063] After washing, it can be filtered and then dried in air in an oven (convection type).

[0064] The reason for washing with an aqueous solution of a lithium compound that is alkaline in an aqueous solution state is to remove LiF and metal fluorides that may be present on the surface of the recovered active material and perform surface modification. During the heat treatment in step S30, the binder and conductive material in the active material layer become CO2 and H2O, which are vaporized and removed. In this process, CO2 and H2O may react with the lithium on the surface of the active material to form Li2CO3 or LiOH, and fluorine (F) present in the binder such as PVdF may react with the metal elements that constitute the positive electrode active material to form LiF or metal fluorides. If LiF or metal fluorides remain, the battery characteristics will deteriorate when the active material is reused. In the present invention, a washing step such as step S40 is added to remove reactants that may have been generated on the surface of the reused active material during the heat treatment step S30, thereby preventing foreign matter from remaining on the surface of the recycled active material.

[0065] In step S40, it is important to wash with an aqueous solution of a lithium compound that is basic in an aqueous solution state. If an aqueous solution of sulfuric acid or hydrochloric acid is used instead of an aqueous solution of a lithium compound that is basic in an aqueous solution state, F on the surface of the active material can be washed away, but transition metals (Co, Mg) present in the active material will be eluted, thereby reducing the performance of the reused positive electrode active material. The aqueous solution of a lithium compound that is basic in an aqueous solution state used in the present invention is highly preferable because it not only removes the binder that may remain in trace amounts even after the thermal decomposition in step S30, but also helps to compensate for the amount of lithium that can be eluted during the washing process without eluting transition metals present in the active material.

[0066] By performing step S40, the present invention makes it possible to adjust the LiF content on the surface of the recovered active material to less than 500 ppm, thereby achieving the effect of improving capacity. Preferably, the F content can be made 150 ppm or less. More preferably, the F content can be made 100 ppm or less. More preferably, the F content can be made 30 ppm or less. According to the present invention, it becomes possible to recover an active material with a reduced F content, and by reusing this as an active material, excellent resistance and capacity characteristics can be realized.

[0067] Next, a lithium precursor is added to the washed active material and annealed (step S50), resulting in a reusable active material.

[0068] During the previous steps S30 and S40, lithium loss may occur in the active material, and in step S50, such lithium loss is compensated for.

[0069] Furthermore, in step S50, the crystal structure of the active material is restored by annealing, and the properties of the reused active material are restored or improved to the level of a fresh active material that has never been used.

[0070] During the previous steps S30 and S40, a deformed structure may appear on the surface of the active material.

[0071] Furthermore, in the case of LCO active material, Co3O4 may be generated on the surface by thermal decomposition. If a battery is manufactured with Co3O4 still present, the battery characteristics may be poor. In the present invention, the crystal structure is restored and Co3O4 is removed in step S50, so that the initial characteristics can be restored or improved to a level similar to that of a fresh active material.

[0072] The lithium precursor in step S50 can be any one or more of LiOH, Li2CO3, LiNO3, and Li2O.

[0073] The lithium precursor is added so that the amount of lithium lost is added to the ratio of lithium to other metals in the raw active material (i.e., fresh active material) used in the active material layer. For example, when the ratio of lithium to other metals in the fresh active material is 1, the lithium precursor can be added so that the amount of lithium added is 0.001 to 0.4 molar ratio. Preferably, the lithium precursor is added so that the amount of lithium added is 0.01 to 0.2 molar ratio. If an excess amount of lithium precursor is added other than the amount of lithium lost by washing, etc., unreacted lithium precursor will remain in the reused active material, which will cause an increase in resistance during the reuse of the active material, so it is necessary to administer an appropriate amount of lithium precursor.

[0074] The annealing may be performed in air at 400-1000°C. The annealing temperature may be 600-900°C. This temperature may vary within a limited range depending on the type of lithium precursor. The annealing time should be at least 1 hour, preferably around 5 hours. If the annealing time is long, the crystal structure will be sufficiently restored, but even if the annealing time is long, it will not have a significant effect on performance. The annealing time is, for example, within 15 hours. The annealing device may be the same as or similar to the device used in the heat treatment step S30.

[0075] For example, when Li2CO3 is used as the lithium precursor, the annealing temperature is preferably 700 to 900°C, more preferably 710 to 780°C. This is because the melting point of Li2CO3 is 723°C. Most preferably, it is 750°C. When LiOH is used as the lithium precursor, the annealing temperature is preferably 400 to 600°C, more preferably 450 to 480°C. This is because the melting point of LiOH is 462°C.

[0076] The annealing temperature is preferably a temperature above the melting point of the lithium precursor, but should not exceed 1000°C, since a temperature above 1000°C may cause thermal decomposition of the positive electrode active material, resulting in a decrease in the performance of the active material.

[0077] Thus, according to the present invention, LiF or metal fluoride is removed in the cleaning step S40, and Co3O4 is removed in the annealing step S50. The cleaning step using an aqueous solution of a lithium compound that is basic in aqueous solution is safe and inexpensive, and can remove LiF or metal fluoride without losing other elements, and has the advantages of preventing the elution of transition metals and the like, as well as compensating for the loss of lithium that occurs during the process. The annealing step is also safe and inexpensive, and has the advantages of effectively removing Co3O4, restoring the crystal structure, i.e., improving the crystallinity, and restoring the battery characteristics of the reused active material.

[0078] The reusable active material obtained by the present invention can have a particle size distribution similar to that of the active material present in the active material layer of the positive electrode plate, so no additional processing is required. Since no carbon components resulting from carbonization of the binder or conductive material remain on the surface, no steps are required to remove such carbon components. Therefore, the active material obtained by the method of FIG. 1 can be reused as it is for the manufacture of a positive electrode without any additional processing.

[0079] The recycled active material can be used as it is without adjusting the composition, or it can be mixed with fresh LCO, and then mixed with a conductive material, a binder, and a solvent to prepare a slurry for use.

[0080] Next, a method according to another embodiment of the present invention will be described with reference to Fig. 2. Fig. 2 shows a lithium composite transition metal oxide (hereinafter simply referred to as "NCM-based, NCA-based, or NCMA-based lithium composite transition metal oxide") in which the positive electrode active material contains nickel (Ni), cobalt (Co), and manganese (Mn) or aluminum (Al).

[0081] Lithium composite transition metal oxides are used as the positive electrode active material of lithium secondary batteries, among which lithium cobalt oxide of LiCoO2, lithium manganese oxide (LiMnO2 or LiMn2O4, etc.), lithium iron phosphate compound (LiFePO4, etc.), or lithium nickel oxide (LiNiO2, etc.) are mainly used. In addition, as a method for improving the low thermal stability while maintaining the excellent reversible capacity of LiNiO2, nickel manganese-based lithium composite metal oxides in which nickel is partially replaced with manganese having excellent thermal stability, NCM-based lithium composite transition metal oxides in which nickel is replaced with manganese and cobalt, NCA-based lithium composite transition metal oxides in which nickel is replaced with cobalt and aluminum, and NCMA-based lithium composite transition metal oxides in which nickel is replaced with cobalt, manganese, and aluminum are used. This embodiment is very suitable for reusing these NCM-based, NCA-based, and NCMA-based lithium composite transition metal oxide active materials.

[0082] 2, a stack cell including a stacked and combined positive electrode plate, a separator, and a negative electrode plate is immersed in a polar solvent to separate the positive electrode plate (step S110). Step S110 can be performed in the same manner as step S10 of FIG. 1 described above.

[0083] Next, the separated positive electrode plate is crushed to an appropriate size (step S120). The positive electrode plate is heat-treated (step S130). Then, the recovered active material is washed (step S140). A lithium precursor is added to the washed active material, and annealed (step S150). Here, steps S120, S130, S140, and S150 can be performed in the same manner as steps S20, S30, S40, and S50 in FIG. 1, respectively.

[0084] In particular, during steps S130 and S140, a deformed structure may appear on the surface of the active material. For example, in the active material that is an NCM-based lithium transition metal composite oxide, Ni may be transformed into a rock salt structure [NiCO3·2Ni(OH2)H2O] by moisture in step S140, forming a spinel structure. If a battery is manufactured in this state, the battery characteristics, such as a decrease in capacity, may deteriorate. In the present invention, the crystal structure is restored in step S150. For example, the active material that is an NCM-based lithium transition metal composite oxide is restored to a hexagonal crystal structure again. This makes it possible to restore or improve the initial characteristics to a level similar to that of a fresh active material.

[0085] Meanwhile, in this embodiment, the method of adding the lithium precursor to the washed active material may be to add the lithium precursor in a solid or liquid phase after drying the washed active material. As another example, the lithium precursor solution may be added to the washed active material and spray-dried, thereby performing drying and adding the lithium precursor in one step. The lithium precursor solution may be a lithium compound that is soluble in an aqueous solution or an organic solvent.

[0086] If drying is performed immediately in an oven or the like after the surface modification process by washing, the active material particles may aggregate and become lumps. In order to mix the lithium precursor with the aggregated particles, grinding of the lumps may be necessary, and in order to mix the solid-phase lithium precursor, powder mixing or milling is required when mixing the materials, which may make the process complicated and difficult to perform continuously. In addition, particularly in the case of NCM-based positive electrode active materials, if powder mixing or milling with the lithium precursor is performed in a state where moisture is present, the positive electrode active material absorbs moisture and the aggregation phenomenon becomes severe. Therefore, in this embodiment, it is proposed to mix and disperse the active material in a lithium precursor solution after washing in step S140, and then spray dry it. This can eliminate the problem of particle aggregation due to drying and the hassle of mixing a solid-phase lithium precursor. In other words, spray drying can have the advantage of producing the material in powder form rather than in lumps.

[0087] In spray drying, the lithium precursor solution dries immediately after spraying, and the lithium precursor components coat or come into contact with the surface of the active material. At this time, there is an advantage that the particles are adjusted by agglomerating due to capillary force when the lithium precursor solution, which is the solvent, dries. When making the electrode, the positive electrode plate is rolled, and the surface particles are pressed and may crack or break. In particular, compared to LCO, NCM-based active materials are more likely to crack due to rolling during electrode formation, so compared to fresh active materials, the recovered active materials contain many small particles, which causes the problem of uneven particles.

[0088] In particular, NCM-based active materials include large particles that are formed by the aggregation of primary particles having a size of tens to hundreds of nm, and a positive electrode made from such an active material may have secondary particles broken into primary particles during rolling to adjust the porosity within the electrode, or may have small particles that are larger than the large particles but smaller than the large particles. The more particles that are broken by rolling, the greater the specific surface area of ​​the active material, so that in the case of reused active materials obtained from rolled electrodes, problems may occur that affect the slurry properties, electrode adhesive strength, and electrode performance when reused.

[0089] In order for the active material to reach a level where it can be reused, it is desirable that its particle size distribution is the same as that of fresh active material. In the spray drying proposed in this embodiment, small particles that are broken during rolling can be solidified and restored to large particles, eliminating particle non-uniformity (variation) and bringing the particle size closer to the initial characteristics of the fresh active material. This effect is particularly noticeable in NCM-based active materials that suffer from severe particle cracking due to the rolling in the previous process. Therefore, it is expected that the battery characteristics of the battery using the active material recovered by the method of the present invention will be similar to those of the battery using the fresh active material.

[0090] As described above, the surface of the active material is coated with the lithium precursor through the spray drying step, and the active material is obtained by adjusting the particles. The addition of the lithium precursor, granulation, and drying are performed in one step, which has the effect of simplifying the process. In addition, spray drying is unique in that it is not just a means for obtaining the active material, but a means for re-granulating particles that have already been used and broken by rolling, etc.

[0091] In addition, since the active material particles washed in the previous step are simply mixed and dispersed in a lithium precursor solution of a certain concentration, washing and spray drying can be performed in a continuous process. Thus, the method for reusing an active material according to this embodiment has the advantage that the process is continuous and lithium precursor coating, drying, and granulation (particle reconditioning) are performed simultaneously in one step.

[0092] On the other hand, in step S150, it is preferable to add the lithium precursor so that the amount of lithium is further added in a molar ratio of 0.0001 to 0.1 based on a molar ratio of lithium to other metals of 1:1. The reason for adding such an excess of lithium is to form a surface protection layer on the active material by surface coating, which will be described later. When a secondary battery is manufactured using such an active material, it is possible to maintain the life characteristics while suppressing side reactions caused by the electrolyte.

[0093] Referring to FIG. 2, the annealed active material is subjected to a surface coating (step S160).

[0094] Depending on the type of active material used initially, some specific elements may be lost during the process, and may be completely removed or only a small amount may remain, especially in step S140, which is a surface modification step by cleaning, so that it may be difficult to fully recover the characteristics only up to the annealing step S150. In such cases, it is desirable to perform step S160, which is an additional surface coating step, as proposed by the present invention. The surface coating can function as a surface protection layer for the positive electrode active material. The surface coating can be a process that replenishes the missing specific elements and at the same time re-forms the surface protection layer that was present on the fresh active material.

[0095] The surface coating step may be a step of coating the surface with at least one of metal, organometallic, and carbon components in a solid or liquid phase manner, followed by heat treatment at 100 to 1200°C. If heat treatment is performed at a temperature exceeding 1200°C, performance may be reduced due to thermal decomposition of the positive electrode active material. In the surface coating, methods such as mixing, milling, spray drying, and grinding may be used to coat the surface in a solid or liquid phase manner.

[0096] A surface protective layer made of a different metal is formed by the surface coating. When the molar ratio of lithium to other metals in the positive electrode active material is set to 1:1, if the lithium in the active material reacts with the surface coating material and the molar ratio of lithium to other metals in the positive electrode active material decreases to less than 1:1, the capacity expression rate will not be 100%. For this reason, not only is the lithium that is insufficient in the previous step S150 added so that the molar ratio of lithium to other metals in the positive electrode active material becomes 1:1, but an excess amount is added so that the lithium with a molar ratio of 0.0001 to 0.1 relative to the other metals in the positive electrode active material is further increased. This makes it possible to form a surface protective layer even when the molar ratio of lithium to other metals in the positive electrode active material becomes 1:1 during the surface coating.

[0097] Specifically, when metal oxides such as B, W, and BW are coated on the active material and then heat-treated, a lithium boron oxide layer can be formed on the surface of the active material, which functions as a surface protection layer. The lithium further added in an amount of 0.0001 to 0.1 molar ratio in step S50 reacts with metal oxides such as B, W, and BW in step S160, and the molar ratio of lithium to other metals in the positive electrode active material does not decrease below 1:1, so that no capacity loss occurs.

[0098] Next, a method according to yet another embodiment of the present invention will be described with reference to Fig. 3. The method of Fig. 3 is suitable for the case where the positive electrode active material is a high content Ni-based (Ni-rich) positive electrode active material, in particular, an NCM-based, NCA-based, or NCMA-based lithium composite transition metal oxide containing a high content of Ni. For example, the nickel content may be 60 mol% or more based on the total moles of the transition metals. Furthermore, the nickel content may be 80 mol% or more based on the total moles of the transition metals.

[0099] 3, the stack cell including the stacked and combined positive electrode plate, separator, and negative electrode plate is immersed in a polar solvent to separate the positive electrode plate (step S210). Step S210 can be performed in the same manner as step S10 of FIG. 1 described above.

[0100] Next, the separated positive electrode plate is crushed into pieces of an appropriate size (step S220). Step S220 can be performed in the same manner as step S20 in FIG.

[0101] Next, the positive electrode plate is heat-treated (step S230). Step S230 can be performed in the same manner as step S30 in FIG. 1. In particular, when a high-content Ni-based positive electrode active material is reused, it is desirable to perform the heat treatment in an oxygen atmosphere for the stability of Ni. O2 with a purity of 80% or more, preferably 90% or more, can be used.

[0102] Then, the recovered active material is washed (step S240). A lithium precursor is added to the washed active material and annealed (step S250). Here, steps S240 and S250 can be performed in the same manner as steps S40 and S50 in FIG. 1 described above. When reusing a high-content Ni-based positive electrode active material during annealing in step S250, it may be desirable to perform the annealing in an oxygen atmosphere for the stability of Ni. O2 with a purity of 80% or more, preferably 90% or more, may be used.

[0103] Next, the annealed active material is washed for the second time (step S260). After the addition of the lithium precursor in step S250, the lithium precursor that could not participate in the reaction exists on the surface of the active material in the form of LiOH and Li2CO3, so a residual lithium removal step is required to remove the lithium precursor. For the secondary washing, water (distilled water) can be preferably used. In particular, in high-content Ni-based positive electrode active materials, as the Ni content increases, lithium impurities, especially lithium carbonate (Li2CO3) impurities, tend to remain on the surface, and these impurities react with the electrolyte to reduce the performance of the battery and generate gas, so they must be strictly controlled. This embodiment includes a first washing step S240 and a second washing step S260, and in particular step S260 is effective in removing residual lithium compounds, making it particularly suitable as a method for reusing high-content Ni-based positive electrode active materials.

[0104] Next, the surface of the active material that has been secondarily washed is coated (step S270). Step S270 can be performed in the same manner as step S160 in Fig. 2. By performing step S270 in this manner, a reusable active material can be obtained.

[0105] Experimental examples of the present invention will now be described in detail.

[0106] <Experimental Example 1: Stack Cell> Figure 4a is a photo of a stack cell. 25 stacks were formed by stacking positive plates, separators, negative plates, etc. The separator is made of a polymer fabric and may shrink due to heat. To prevent this, the separator fabric is coated with ceramic particles of tens to hundreds of nanometers. During lamination, the ceramic particles of the separator are transferred to the positive plate, and the positive plate is rolled. In this experimental example, the ceramic particles were Al2O3.

[0107] Figure 4b is a photograph of the positive electrode plate before the stack cell is constructed. The positive electrode plate is black in color.

[0108] FIG. 4c is a front photograph of a positive plate in a state where the negative plate and the separator are only physically separated after forming a stack cell, and FIG. 4d is a rear photograph of the positive plate. Compared to FIG. 4b, there are many white parts on the positive plate. The white parts are the ceramic particles of the separator that have been transferred. The ceramic particles are pressed by the lamination process when the positive plate and the separator are combined, and are transferred to the positive plate. However, when the positive plate and the separator are only physically separated, it has been confirmed that the ceramic particles transferred to the surface of the positive plate remain on the positive plate as they are. If such a positive plate is subjected to a recycling process, the ceramic particles remain in the recovered recycled active material, which causes problems.

[0109] <Experimental Example 2: Heat treatment without immersion in a polar solvent> The positive electrode plate shown in Figures 4c and 4d was subjected to the heat treatment of step S30 in Figure 1. The heat treatment was performed at 550°C for 0.5 hours, with a temperature increase of 5°C / min and air flow of 3L / min. This removed the binder and conductive material components in the positive electrode active material layer, and the active material was released from the current collector.

[0110] FIG. 5 is a photograph of the active material recovered after such heat treatment. The positive active material detached from the positive electrode current collector of the positive electrode plate is black, and the white part is a layer of ceramic particles that remain after being transferred from the separation membrane. Even if the active material of FIG. 5 containing the layer of ceramic particles is sieved with a 325 mesh, the ceramic particles of several hundred nanometers are filtered out together and cannot be separated from the active material. Therefore, as proposed by the present invention, it is necessary to perform a step of immersion in a polar solvent, which is a step of removing ceramic particles, before performing the heat treatment step.

[0111] <Experimental Example 3: Effect of immersion in polar solvent 1>. A step corresponding to step S10 in FIG. 1 was carried out using the positive electrode plate shown in FIG. 4c and FIG. 4d.

[0112] When coating the ceramic particles on the separation membrane, a coating liquid is used that is made by adding a binder, ceramic particles, and a dispersant to a highly volatile solvent to achieve a thin, fast-drying coating. If the stack cell is immersed in the same polar solvent as the solvent used to manufacture the separation membrane, the ceramic particles will fall off into the polar solvent. The polar solvent used in this embodiment was acetone.

[0113] Figure 6 shows a photo of the positive electrode plate, which was immersed in acetone for a certain period of time after the stack cell was formed and the negative electrode plate and separator were only physically separated from each other. As the ceramic particles were separated from the positive electrode plate, the black part of the positive electrode plate was exposed.

[0114] <Experimental Example 4: Effect of immersion in polar solvent 2> The stack cell shown in FIG. 4a was immersed in acetone, and step S10 in FIG. 1 was performed.

[0115] Figure 7a is a photograph of the stack cell immersed in acetone. Figure 7b is a photograph of the positive electrode plate being lifted from the stack cell after a certain time has passed. Unlike Figures 4c and 4d, it can be seen that the ceramic particles have been transferred and the black positive electrode plate without any white areas is neatly separated from the separator.

[0116] Figure 7c is a photograph of a fully separated positive plate from such a stack cell, and in comparison with Figures 4c and 4d, it can be seen that there is a significant reduction in the amount of ceramic particle residue on the surface of the positive plate after final separation.

[0117] <Experimental Example 5: Separated charge / discharge experiment of stack cell having NCM-based positive electrode active material> Comparative Example 1: A fresh active material of an NCM-based lithium transition metal composite oxide.

[0118] Example 1: A reused active material was obtained by performing all the steps of the method of the present invention. Specifically, steps S110, S120, S130, S140, S150 and S160 of the method described with reference to FIG. 2 were performed. First, the stack cell was immersed in acetone to separate the positive plate, and the positive plate was heat-treated at 550°C / 0.5 hours, with a temperature rise of 5°C / min and air of 3L / min to separate the active material. The active material was washed with LiOH for 10 minutes. Based on the molar ratio of lithium to other metals in the raw active material (ICP: Inductively Coupled Plasma) analysis, a lithium precursor (LiOH) was added to the active material so that 0.09 molar ratio of lithium was further added during the process, and annealed at 750°C for 15 hours. After that, 1000 ppm of H3BO3 was added to add boron, and a coating step was performed at 300°C for 5 hours with an increase rate of 2°C / min and air of 3 L / min.

[0119] Example 2: The positive electrode active material was recovered so as to be recyclable in the same manner as in Example 1. However, the amount of lithium precursor added in step S150 was increased to 0.10 mol.

[0120] Example 3: The positive electrode active material was recovered in the same manner as in Example 1. However, the amount of lithium precursor added in step S150 was increased to 0.11 mol.

[0121] Comparative Example 2: Step S110 of the method described with reference to FIG. 2 was not performed. In other words, after the positive electrode plate was only physically separated from the stack cell, the same process as in Example 2 was carried out from step S120.

[0122] The positive electrode active material recovered or prepared in each of the Examples and Comparative Examples was weighed out at 96.25 wt%, carbon black as a conductive material at 1.5 wt%, and PVdF as a binder at 2.25 wt%, and mixed with NMP to prepare a slurry. A positive electrode was manufactured using the slurry, and then a coin half cell (CHC) was manufactured to evaluate the electrochemical performance.

[0123] FIG. 8 shows the results of cell evaluation using the active materials of the examples and comparative examples. The rate performance was investigated by evaluating the capacity according to the number of cycle repetitions at different currents. The device used for the evaluation was a general charge / discharge experimental device commonly used in laboratories. There was no deviation due to the measurement device or method. In the graph of FIG. 8, the horizontal axis indicates the number of cycles, and the vertical axis indicates the capacity.

[0124] The voltage conditions were 3 to 4.3 V, and charging and discharging were performed at 0.1 C / 0.1 C-0.33 C / 0.33 C-0.5 C / 0.1 C-0.5 C / 1 C-0.5 C / 2 C. The electrolyte used to make up the cell was a carbonate-based solution with ethylene carbonate (EC): ethyl methyl carbonate (EMC) = 3:7, which also contained some additive (LiPF6).

[0125] Table 1 shows the charge capacity, discharge capacity, and efficiency of the examples and comparative examples, as well as the efficiency compared to Comparative Example 1.

[0126] [Table 1]

[0127] Referring to Fig. 8 and Table 1, Comparative Example 2 shows a result in which the charge / discharge capacity is 7 mAh / g or more lower than Examples 1 to 3. That is, when the positive electrode plate to which the ceramic particles are transferred is only physically separated from the stack cell as in Comparative Example 2 and the steps of the method for reusing an active material proposed by the present invention are carried out while the transferred ceramic particles are still held, the mixing ratio of the ceramic particles is higher than when a process such as immersion in acetone is also carried out, and such a result was obtained. The decrease in charge / discharge capacity occurs due to an increase in resistance caused by the ceramic particle component.

[0128] Thus, according to Examples 1 to 3, the capacity expression rate can be increased compared to Comparative Example 2 by separating the ceramic particles by immersion in acetone or the like.

[0129] <Experimental Example 6: Separate charge / discharge experiment of stack cell having LCO positive electrode active material> Comparative Example 3: LCO is a fresh active material.

[0130] Example 4: A reused active material was obtained by carrying out all the steps of the method of the present invention. Specifically, steps S10, S20, S30, S40 and S50 of the method described with reference to FIG. 1 were carried out. The stack cell was immersed in acetone to separate the positive plate, and the positive plate was heat-treated at 550°C / 0.5 hours, with a temperature rise of 5°C / min and air flow of 3L / min. The active material thus obtained was washed with LiOH for 10 minutes. A lithium precursor (Li2CO3) with a lithium amount of 2 mol% excess compared to the lithium amount of the reused LCO was added, and annealed at 750°C for 15 hours.

[0131] Comparative Example 4: Step S10 of the method described with reference to FIG. 1 was not performed, that is, after the positive electrode plate was only physically separated from the stack cell, the same process as in Example 4 was carried out from step S20.

[0132] The positive electrode active material recovered or prepared in each of the Examples and Comparative Examples was weighed out at 96 wt%, carbon black as a conductive material at 2 wt%, and PVdF2 as a binder at 5 wt%, and mixed with NMP to prepare a slurry. A positive electrode was manufactured using the slurry, and then a cell (CHC) was manufactured and its electrochemical performance was evaluated.

[0133] Figure 9 shows the results of cell evaluation using the active materials of the examples and comparative examples. The rate performance was investigated by evaluating the capacity according to the number of cycles repeated at different currents. In the graph of Figure 9, the horizontal axis indicates the number of cycles, and the vertical axis indicates the capacity.

[0134] The voltage conditions were 3 to 4.55 V, and charging and discharging were performed at 0.2 C / 0.2 C-0.1 C / 0.1 C-0.5 C / 0.2 C-0.5 C / 1 C-0.5 C / 2 C-0.5 C / 1 C. The electrolyte used to make up the cell was a carbonate-based solution with a ratio of ethylene carbonate (EC): dimethyl carbonate (DMC): ethyl methyl carbonate (EMC) = 3:4:3, which also contained some additive (LiPF6).

[0135] Table 2 shows the charge capacity, discharge capacity, and efficiency of the examples and comparative examples, as well as the efficiency compared to Comparative Example 3.

[0136] [Table 2]

[0137] 9 and Table 2, Comparative Example 4 shows a result in which the charge / discharge capacity is inferior to Example 5. That is, when the positive electrode plate to which the ceramic particles are transferred is only physically separated from the stack cell as in Comparative Example 4 and the steps of the method for reusing an active material proposed by the present invention are carried out while the transferred ceramic particles are still held, the mixing ratio of the ceramic particles is higher than when a process such as immersion in acetone is also carried out, and this result was obtained because the ceramic particle components increase resistance, resulting in a decrease in charge / discharge capacity.

[0138] Thus, according to Example 5, the capacity expression rate can be increased compared to Comparative Example 4 by separating the ceramic particles by immersion in acetone or the like.

[0139] <Experimental Example 7: Confirmation of the effectiveness of the method for reusing LCO positive electrode active material> Positive electrode active materials were prepared in the same manner as in the following Examples and Comparative Examples, and the amount of residual LiF, electrochemical performance, and the like were evaluated.

[0140] Comparative Example 5: Fresh LCO was used instead of reused active material. This is a different active material from that of Comparative Example 3.

[0141] Example 6: Specifically, steps S10, S20, S30, S40 and S50 of the method described with reference to FIG. 1 were carried out. After preparing a stack cell including a positive electrode plate made of the same positive electrode active material as in Comparative Example 5, the stack cell was immersed in acetone to separate the positive electrode plate, and the positive electrode plate was heat-treated in air at 550°C for 0.5 hours. Cleaning was carried out for 10 minutes using LiOH. A lithium precursor (Li2CO3) with a lithium amount of 2 mol% excess compared to the lithium amount of the reused LCO was added, and annealed at 750°C for 15 hours.

[0142] Comparative Example 6: In the above-mentioned method for reusing an active material according to the present invention, only the heat treatment in step S30 was performed, the binder and conductive material were removed, and the Al current collector was separated to recover the LCO active material. Step S30 was performed under the same conditions as in Example 6. In the method for reusing an active material according to the present invention, the surface modification in step S40 and the recovery of the crystal structure in step S50 were not performed.

[0143] Comparative Example 7: Further progressing from Comparative Example 6, the surface modification of step S40 in the method for reusing an active material according to the present invention was carried out, and the LCO active material was recovered. That is, the surface modification was carried out, but the crystal structure recovery of step S50 in the method for reusing an active material according to the present invention was not carried out. Step S40 was carried out under the same conditions as in Example 6.

[0144] In order to grasp the amount of LiF remaining in the active materials recovered in Comparative Examples 6 and 7, F was detected and analyzed by ICP. The F content was measured to be 1450 mg / kg in Comparative Example 6, and 30 ppm or less in Comparative Example 7. It was confirmed that the F content in the recovered positive electrode active material in Comparative Example 7 was significantly lower than that in Comparative Example 6. In other words, LiF was completely dissolved in the lithium compound aqueous solution by washing, and was removed to a level that could not be detected by ICP. Therefore, it can be seen that LiF removal by step S40 is excellent.

[0145] The positive electrode active material recovered or prepared in each of the Examples and Comparative Examples was weighed out at 96 wt%, carbon black as a conductive material at 2 wt%, and PVdF as a binder at 2 wt%, and mixed with NMP to prepare a slurry. A positive electrode was manufactured using the slurry, and then a cell was manufactured and its electrochemical performance was evaluated.

[0146] FIG. 10 shows the results of cell evaluation using the active materials of the examples and comparative examples. The rate performance was investigated by evaluating the capacity according to the number of cycle repetitions at different currents. The device used for the evaluation was a general charge / discharge experimental device commonly used in laboratories. There was no deviation due to the measurement device or method. In the graph of FIG. 10, the horizontal axis is the number of cycles, and the vertical axis is the capacity.

[0147] The voltage condition was 3 to 4.5 V, and the initial formation charge and discharge was performed at 0.2° C. / 0.2° C. The electrolyte constituting the cell was EC:EMC=3:7, and contained some additives.

[0148] 10, it can be seen that the lowest rate performance is that of Comparative Example 6, which is a reused active material but does not undergo surface modification and crystal structure recovery according to the present invention. This is because, when the binder and conductive material are removed with CO2 and H2O during the high-temperature heat treatment process such as step S30, Li2CO3 and LiOH react with the lithium on the surface of the positive electrode active material to form Li2CO3 and LiOH, which react with F present in the binder to form LiF or metal fluoride. It is also believed that the poor battery performance is due to Co3O4 produced by thermal decomposition of the LCO surface.

[0149] In Comparative Example 7, surface modification was performed, unlike Comparative Example 6. In Comparative Example 7, the reaction product generated on the surface was removed by washing, and therefore it is evaluated that better results were obtained than in Comparative Example 6.

[0150] Unlike Comparative Example 7, Example 6 was annealed. Li2CO3 was added and annealed to compensate for the lithium lost during the active material recovery process and to restore crystallinity. Not only was it possible to compensate for the lithium deficiency that occurred during this process, but it was also confirmed that the deformed structure and Co3O4 that appeared on the active material surface during regeneration were reduced back to the LCO crystal structure, resulting in improved results compared to the initial characteristics of the fresh active material of Comparative Example 5.

[0151] Thus, according to the present invention, it is possible to recover active materials from cathode scraps to a level that allows them to be directly reused. This process is safe because it does not use toxic and explosive solvents such as NMP, DMC, and methanol, and is suitable for mass production by utilizing simple and safe methods such as heat treatment, washing and drying, and annealing.

[0152] FIG. 11 shows X-ray diffraction (XRD) patterns of the active materials of the examples and the comparative examples. In the XRD patterns, the horizontal axis is 2θ (Theta) (degrees) and the vertical axis is intensity. The XRD patterns were obtained using a general X-ray diffraction device that is often used in laboratories. For example, Rigaku's XG-2100 X-ray diffraction device can be used for the analysis. However, there is no deviation due to the device or method.

[0153] 11, (a) is the XRD pattern of Comparative Example 5, i.e., fresh LCO, (b) is the XRD pattern of the active material of Comparative Example 6, and (c) is the XRD pattern of the active material of Comparative Example 7. Comparing (b) and (c) with (a), the Co3O4 phase is confirmed. That is, it can be confirmed that Co3O4 is generated on the surface of the LCO during the heat treatment process in step S30.

[0154] FIG. 11(d) is an XRD pattern of the active material of Example 6. Comparing (c) and (d), it can be seen that the annealing in step S50 has caused the Co3O4 phase to disappear and the crystal structure to recover to LCO. Looking at the positions of the diffraction peaks in the XRD pattern, the crystal structure of (d) is similar to that of (a). Therefore, it can be seen that Example 6 according to the present invention has recovered to the level of the fresh active material of Comparative Example 5. Thus, according to the present invention, it is possible to recover the positive electrode active material from the stack cell to a level where it can be directly reused.

[0155] FIG. 12 shows SEM photographs of the active materials of the examples and the comparative examples. The SEM photographs were taken using a common SEM device commonly used in laboratories. For example, they can be taken using S-4200 manufactured by HITACHI. However, there is no deviation due to the measurement device or method.

[0156] In FIG. 12, (a) is an SEM photograph of fresh LCO of Comparative Example 5, and (b) is an SEM photograph of the reused active material of Example 6. It can be confirmed that the recovered LCO of the Example also has the same shape as the fresh LCO. Furthermore, since only LCO is observed, it can be confirmed that the binder and conductive material were removed during the high-temperature heat treatment process. Therefore, it can be seen that the active material is separated from the current collector only by heat treatment in air, and almost no binder or conductive material remains on the surface of the active material. Thus, according to the present invention, the active material can be separated from the current collector without using complicated methods or harmful substances, and the active material can be recovered in an environmentally friendly manner. In addition, since it can be reused without using acid, a neutralization process and a wastewater treatment process are not required, which alleviates environmental problems and reduces process costs.

[0157] FIG. 13 is a graph showing the particle size distribution of the active materials of the examples and the comparative examples. The particle size distribution can be determined using a general particle size distribution measuring device that is often used in laboratories. For example, it can be measured using a particle size distribution measuring device LA-950V2 manufactured by Horiba. However, there is no deviation due to the measuring device or measuring method. In FIG. 13, the horizontal axis is particle size (μm) and the vertical axis is volume %.

[0158] The active materials recovered in Example 6 and Comparative Examples 6 and 7 all have similar particle size distributions compared to the fresh LCO of Comparative Example 5. Particle size distributions are defined as similar when the volume percentages of particles having the same particle size (particle size) differ only within a range of ±2%. Thus, according to the present invention, the particle size distribution of the active material does not change, so the initial characteristics are almost maintained, and the characteristics of a battery using this material can be expected to be at a similar level to the characteristics of a battery using fresh active material.

[0159] In addition to the LCO positive electrode active material, the method according to the present invention was also applied to an NCM-based positive electrode active material to obtain and confirm reused active materials. As a result, it was found that the method according to the present invention can obtain reused active materials of similar quality to fresh active materials.

[0160] <Experimental Example 8: Confirmation of the effect of the method of reusing NCM-based positive electrode active material> Example 7: Steps S110, S120, S130, S140 and S150 of the method described with reference to FIG. 2 were performed. First, the stack cell was immersed in acetone to separate the positive electrode plate, and the positive electrode plate was heat treated at 550°C / 0.5 hours, with an increasing temperature of 5°C / min and air of 3L / min to separate the active material. The active material was washed with LiOH for 10 minutes. Based on the molar ratio of lithium to other metals in the raw active material (ICP analysis), a lithium precursor (Li2CO3) was added to the active material so that 0.09 molar ratio of lithium was further added during the process, and annealed at 750°C for 15 hours. Theoretically, in the case of fresh active material, the molar ratio of lithium to other metals is 1:1, but the average error of the ICP device that confirms this is about ±0.05, preferably about ±0.02, so that the molar ratio of lithium to other metals in the raw active material measured by ICP measurement may be 1±0.05:1. In this experiment, the lithium precursor was added based on the ratio analyzed by ICP analysis.

[0161] Example 8: In addition to Example 7, the active material surface protection layer recovery step of step S160 in Fig. 2 was also performed. To add boron, 1000 ppm of H3BO3 was added, and a coating step was performed at 300°C for 5 hours, with an increase rate of 2°C / min and air of 3L / min.

[0162] Comparative Example 8: Fresh NCM-based lithium transition metal composite oxide was used instead of a reused active material.

[0163] Comparative Example 9: In the above-mentioned method for reusing an active material according to the present invention, only the heat treatment in step S130 was carried out, the binder and conductive material were removed, and the Al current collector was separated to recover an NCM-based lithium transition metal composite oxide active material. Step S130 was carried out under the same conditions as in Example 7. In the method for reusing an active material according to the present invention, the cleaning in step S140, the annealing in step S150, and the surface coating step in step S160 were not carried out.

[0164] Comparative Example 10: Further progressing from Comparative Example 9, the above-mentioned method for reusing an active material according to the present invention was followed up to the washing step S140, and the active material was recovered. That is, the surface was modified, but the crystal structure recovery step S150 and the surface coating step S160 of the method for reusing an active material according to the present invention were not carried out. Step S140 was carried out under the same conditions as in Example 7.

[0165] Comparative Example 11: Further progressing from Comparative Example 9, in the above-mentioned method for reusing an active material according to the present invention, the surface modification in step S140 was not performed, and only the recovery of the crystal structure in step S150 was performed to recover an NCM-based lithium transition metal composite oxide active material. Unlike Example 7, the annealing for recovering the crystal structure was performed without adding a lithium precursor.

[0166] Comparative Example 12: Similar to Example 7, only steps S130, S140, and S150 were performed. However, unlike Example 7, the annealing for recovering the crystal structure was performed without adding a lithium precursor.

[0167] The positive electrode active materials recovered or prepared in the above Examples and Comparative Examples were subjected to ICP analysis to analyze the ratio of lithium and other metals in the active materials and the amounts of specific elements such as B and W.

[0168] Then, 96.25 wt% of the positive electrode active material recovered or prepared in each of the Examples and Comparative Examples, 1.5 wt% of carbon black as a conductive material, and 2.25 wt% of PVdF as a binder were weighed out and mixed with NMP to prepare a slurry, which was then used to manufacture a positive electrode, and a cell (CHC) was manufactured to evaluate its electrochemical performance.

[0169] In order to determine whether the lithium content in the positive electrode active material was changed during steps S130 and S140 of the present invention, the ratio of lithium to other metals in the active material was analyzed by ICP. The results are shown in Table 3 below.

[0170] [Table 3]

[0171] Referring to Table 3, it can be seen that the lithium / other metal ratio in Comparative Example 9 was reduced by about 0.2 to 0.5 compared to Comparative Example 8 during the heat treatment of S130, and was reduced by about 0.2 to 0.5 in Comparative Example 10 compared to Comparative Example 9 during the washing and drying of S140. This shows that the NCM-based lithium transition metal composite oxide has a relatively large particle specific surface area, and the lithium ratio to other metals is significantly reduced due to the change to a spinel structure. Therefore, it can be seen that it is necessary to make up for the lack of lithium.

[0172] Table 3 shows the measured values ​​by ICP analysis, but as mentioned above, there is an error of about ±0.02. Therefore, even in Comparative Example 8, which is a fresh active material, the ratio of lithium to other metals may be less than 1. Therefore, the amount of lithium precursor added to compensate for the lost lithium is based on the ratio of lithium to other metals (molar ratio determined by ICP analysis) in the raw active material (i.e., fresh active material) used in the active material layer, so that the lithium content can be added to the extent that it is reduced.

[0173] Figures 14 and 15 show the results of cell evaluation using the active materials of the examples and comparative examples. The rate performance was investigated by evaluating the capacity according to the number of cycle repetitions at different currents. The equipment used for the evaluation was a general charge / discharge experimental equipment commonly used in laboratories. There was no deviation due to the measurement equipment or method. In the graphs of Figures 14 and 15, the horizontal axis indicates the number of cycles, and the vertical axis indicates the capacity.

[0174] The voltage conditions were 3 to 4.3 V, and the initial formation charge and discharge was performed at 0.1 C / 0.1 C. The electrolyte used to make up the cell was a carbonate-based electrolyte with an EC:EMC ratio of 3:7 that contained some additives.

[0175] 14, after the first heat treatment (550° C. / 30 min) for desorption, a comparison between Comparative Example 9 before surface modification and Comparative Example 10 after surface modification reveals that the electrode capacity of Comparative Example 10 after surface modification is rapidly reduced. This is because, as described above, Ni in the NCM-based lithium transition metal composite oxide is converted to hydrochloride by moisture, resulting in a reduction in capacity.

[0176] However, when annealing (750°C / 15 hours) was performed without surface modification, the result was equivalent to Comparative Example 11, and almost no improvement in capacity was observed compared to Comparative Example 9. This is because LiF remains on the active material surface when surface modification is not performed. This is demonstrated in the above-mentioned Experimental Example 7 that cleaning is necessary to remove LiF to a satisfactory level.

[0177] When surface modification and annealing are performed after the primary heat treatment, the capacity increases as shown in Comparative Example 12. This is because, although the capacity decreases after the surface modification process as in Comparative Example 10, after LiF is removed by the surface modification, Ni rock salt is reduced by annealing, and the structure is restored to a hexagonal crystal.

[0178] Next, referring to FIG. 15, the capacity improvement of Example 7 compared to Comparative Example 12 is confirmed. Example 7, compared to Comparative Example 12, adds a lithium precursor during annealing. It can be seen that the addition of such a lithium precursor improves capacity by replenishing lithium lost in the previous step. The loss of lithium during heat treatment and washing was described with reference to Table 3.

[0179] The lithium compound was added in an amount equal to the ratio of the lost lithium to the lithium content in the original positive electrode active material based on the results of ICP analysis (Table 3), and further experiments confirmed that the addition of a 0.09-0.1 molar ratio resulted in a capacity improvement at a level equivalent to that of Comparative Example 8.

[0180] Thus, according to the present invention, it is possible to recover active materials from cathode scraps to a level that allows them to be directly reused. This process is safe because it does not use toxic and explosive solvents such as NMP, DMC, and methanol, and is suitable for mass production by utilizing simple and safe methods such as heat treatment, washing and drying, and annealing.

[0181] The positive electrode active materials recovered or prepared in the above Examples and Comparative Examples were each subjected to ICP analysis to analyze the amounts of specific elements. The results are shown in Table 4 below.

[0182] [Table 4]

[0183] The fresh active material used in this experiment contained more B and W, as shown in Comparative Example 8. In Comparative Example 9, the contents of B and W were reduced by heat treatment, and the remaining results show that B was almost completely removed in the subsequent process. ND means a measured value of 30 ppm or less. In the case of W, it can be seen that a large amount is removed during the surface modification by cleaning, as shown in Comparative Example 10.

[0184] Therefore, depending on the type of active material used initially, some specific elements may be lost during the process, and in particular, there may be cases where they are completely removed or only a small amount remains during the surface modification process by cleaning, so there may be cases where it is difficult to fully recover the characteristics only by the annealing step as in Example 7. In such cases, it is desirable to add a surface coating step S160 as proposed by the present invention. In this experimental example, the surface coating step is to coat B and W. The surface coating can function as a surface protection layer for the positive electrode active material. The surface coating can be a process of replenishing a specific element that is missing and at the same time rebuilding the surface protection layer of the fresh active material. In the case of the fresh active material used in this experiment, the surface protection layer is BW, and the amount of lithium lost during the process is interpreted as the ratio of the lithium of the active material itself to other metals is not 1:1, but the ratio of (lithium of the active material itself + lithium for forming the surface protection layer): other metals. Therefore, as shown in Comparative Example 10 in the above experiment, the lost 0.09 molar ratio can be interpreted as the combined amount of lithium in the positive electrode active material and the lithium for forming the surface protective layer, and in the examples, a lithium precursor was added to compensate for that amount of lithium.

[0185] <Experimental Example 9: Confirmation of the effect of the method of reusing high Ni content NCM-based positive electrode active material>. Comparative Example 13: A fresh active material of a high Ni content NCM-based lithium transition metal composite oxide.

[0186] Example 9: A reused active material was obtained by performing all the steps of the method of the present invention. Specifically, steps S210, S220, S230, S240, S250, S260 and S270 of the method described with reference to FIG. 3 were performed. The stack cell was immersed in acetone to separate the positive plate, and the positive plate was heat treated at 550°C / 0.5 hours, with a temperature rise of 5°C / min and O23L / min. The active material thus obtained was washed twice in step S240. The first time, the ratio of active material:washing solution was 1:30, and the mixture was stirred at 300 rpm for 10 minutes, and then only the active material was taken out using a reduced pressure filter. The second time, the mixture was washed at a ratio of active material:washing solution = 1:10. Next, 0.11 moles of LiOH, a lithium precursor, was added, and annealing was performed in step S250 of the method for reusing a positive electrode active material according to the present invention by supplying O2 at 3 L / min at 750°C / 5 hours. Then, a water washing step S260 was performed to remove the surface residual lithium. The water washing was performed by stirring the active material: water washing solution = 1:1 at 300 rpm for 1 minute, filtering under reduced pressure, and then vacuum drying (130°C drying) overnight. Then, 1000 ppm of H3BO3 was added to add boron, and step S270 was performed to coat the material at 300°C / 5 hours, at an increase rate of 2°C / min, and with air at 3 L / min.

[0187] Example 10: A positive electrode active material was recovered in the same manner as in Example 9. However, the amount of lithium precursor added in step S250 was increased to 0.13 mol.

[0188] Example 11: A positive electrode active material was recovered in the same manner as in Example 9. However, the amount of lithium precursor added in step S250 was increased to 0.15 mol.

[0189] Example 12: A positive electrode active material was recovered in the same manner as in Example 9. However, the amount of lithium precursor added in step S250 was increased to 0.17 mol.

[0190] Comparative Example 14: Similar to Example 9, except that the secondary cleaning step, ie, step S260, was not performed.

[0191] Comparative Example 15: Similar to Example 10, except that the secondary cleaning step, ie, step S260, was not performed.

[0192] Comparative Example 16: Similar to Example 11, except that the secondary cleaning step, ie, step S260, was not performed.

[0193] 96.25% by weight of the positive electrode active material, 1.5% by weight of carbon black as a conductive material, and 2.25% by weight of PVdF as a binder were weighed out and mixed in NMP to prepare a slurry. A positive electrode was manufactured using this, and then a cell (CHC) was manufactured and its electrochemical performance was evaluated. Figures 16 and 17 show the results of cell evaluation using the active materials of the examples and comparative examples. The rate performance was investigated by evaluating the capacity according to the number of cycle repetitions at different currents. The equipment used for the evaluation was a general charge / discharge experimental equipment commonly used in laboratories. There was no deviation due to the measurement equipment or method. In the graphs of Figures 16 and 17, the horizontal axis indicates the number of cycles, and the vertical axis indicates the capacity.

[0194] The voltage conditions were 3 to 4.3 V, and charging and discharging were performed at 0.1 C / 0.1 C-0.33 C / 0.33 C-0.5 C / 0.1 C-0.5 C / 1 C-0.5 C / 2 C. The electrolyte used to make up the cell was a carbonate-based electrolyte with an EC:EMC ratio of 3:7, but which also contained some additives.

[0195] 16 shows a comparison between Comparative Example 13, which is a fresh active material, and Examples 9 to 12. Table 5 shows a summary of the charge capacity, discharge capacity, and efficiency.

[0196] [Table 5]

[0197] 16 and Table 5, in the embodiment of the present invention, when the lithium precursor was added, annealed, and the surface residual lithium precursor was removed by secondary cleaning, the charge / discharge capacity was at the same level as that of a fresh active material. When an excess amount of lithium was added compared to the amount of lithium lost during the process (0.11 moles), that is, in the case of Example 9, Examples 10 to 12 had a higher capacity expression rate. It was confirmed that not only the initial capacity but also the C-rate capacity was at the same level as that of a fresh active material.

[0198] Next, Fig. 17 shows a comparison between Comparative Example 13 and Comparative Examples 14 to 16. Comparative Examples 14 to 16 did not undergo a secondary cleaning step after annealing. Table 6 summarizes the charge capacity, discharge capacity, and efficiency.

[0199] [Table 6]

[0200] 17 and Table 6, it can be seen that even if annealing is performed after the addition of the lithium precursor, if the lithium precursor remaining on the surface is not subsequently removed, a lower capacity expression rate is shown compared to a fresh active material. There is no difference in initial capacity between the amount of lithium lost during the process (0.11 mol) and the amount of lithium added in excess, but at high C rates, the capacity is slightly higher with the amount of lithium added in excess.

[0201] The amount of residual lithium before and after washing the surface residual lithium precursor was analyzed. For Comparative Example 13, Example 11, Example 12, and Comparative Example 16, 5 g of each active material was taken, dispersed in 100 ml of distilled water, stirred at 300 rpm for 5 minutes, and then the active material was filtered through a filter. The obtained solution was titrated with 0.1 M HCl solution to calculate the pH and the concentration of LiOH and Li2CO3 dissolved from the active material. The solvent (NMP) becomes alkaline due to the excess LiOH dissolved in the solvent during electrode preparation. The alkaline solvent mixes with the binder and gelates the slurry, making it impossible to prepare an electrode. In addition, the excess Li2CO3 is easily attacked by HF generated by a very small amount of water molecules present in the electrolyte, and decomposes to generate gas. Therefore, it is necessary to remove lithium compounds that supply residual lithium, such as LiOH and Li2CO3.

[0202] [Table 7]

[0203] When the surface residual lithium is not removed as in Comparative Example 16, the total residual lithium content is 0.823 wt% Li, whereas when the surface residual lithium is removed as in Examples 11 and 12 according to the present invention, it can be confirmed that the residual lithium is controlled to a level similar to that of Comparative Example 13.

[0204] As described above, according to the present invention, the positive electrode active material can be recovered from the stack cell in a simple, environmentally friendly, and economical manner and reused. Even if a lithium secondary battery is manufactured using the resulting reused positive electrode active material, there is no problem with the battery performance.

[0205] Although the present invention has been described above using limited embodiments and drawings, the present invention is not limited thereto, and it goes without saying that various modifications and variations are possible within the scope of the technical spirit of the present invention and the scope of the claims.

Claims

1. Immersing a stack cell including the stacked and combined positive electrode plate, the separator coated with ceramic particles, and the negative electrode plate in acetone to separate the positive electrode plate; a step of subjecting the separated positive electrode plate to a heat treatment to thermally decompose the binder and the conductive material in the positive electrode active material layer of the positive electrode plate, thereby separating the current collector of the positive electrode plate from the positive electrode active material layer and recovering the active material in the positive electrode active material layer; washing the recovered active material with an aqueous solution of a lithium compound that is basic in an aqueous solution to remove LiF, metal fluorides, and binders, and replenishing lithium; adding a lithium precursor to the washed active material and annealing to obtain a reusable active material.

2. The method for reusing a positive electrode active material according to claim 1 , further comprising the step of surface-coating the annealed active material.

3. The method for reusing a positive electrode active material according to claim 1 , further comprising the step of surface-coating the annealed active material after cleaning it.

4. 2. The method for reusing a positive electrode active material according to claim 1, wherein the heat treatment is carried out in air or an oxygen atmosphere at 300 to 650° C.

5. The method for reusing a positive electrode active material according to claim 1 , wherein the lithium compound aqueous solution is prepared so as to contain more than 0% and not more than 15% of a lithium compound.

6. 2. The method for reusing a positive electrode active material according to claim 1, wherein the washing is performed by immersing the recovered active material in the aqueous lithium compound solution while stirring the same.

7. The lithium precursors used in the annealing are LiOH, Li 2 CO 3 , LiNO 3 and Li 2 The method for reusing a positive electrode active material according to claim 1 , wherein the positive electrode active material is one or more of O.

8. 2. The method for reusing a positive electrode active material according to claim 1, wherein the lithium precursor is added in an amount corresponding to a ratio of lost lithium relative to a ratio of lithium and other metals in a raw active material used for the positive electrode active material layer.

9. The method for reusing a positive electrode active material according to claim 8, wherein the lithium precursor is added so that lithium is added in an amount of 0.001 to 0.4 molar ratio.

10. The method for reusing a positive electrode active material according to claim 8, wherein the lithium precursor is added so that lithium is further added in an amount of 0.0001 to 0.1 molar ratio based on a molar ratio of lithium to other metal of 1:

1.

11. 2. The method for reusing a positive electrode active material according to claim 1, wherein the annealing is carried out in air or an oxygen atmosphere at 400 to 1000° C.

12. The method for reusing a positive electrode active material according to claim 1 , wherein the annealing temperature is a temperature exceeding the melting point of the lithium precursor.

13. 2. The method for reusing a positive electrode active material according to claim 1, wherein the active material in the positive electrode active material layer is recovered in a powder form, and no carbon component resulting from carbonization of the binder or conductive material remains on the surface.

14. 4. The method for reusing a positive electrode active material according to claim 2 or 3, wherein the surface coating is performed by coating the surface with at least one of a metal, an organic metal, and a carbon component in a solid or liquid phase manner, and then heat-treating the surface at 100 to 1200° C.

15. 4. The method for reusing a positive electrode active material according to claim 3, wherein the positive electrode active material is a lithium transition metal oxide containing nickel, cobalt, and manganese or aluminum, and a content of the nickel is 60 mol % or more based on a total mole number of the transition metals.

16. 2. The method for reusing a positive electrode active material according to claim 1, wherein the reusable active material has a fluorine (F) content of 100 ppm or less.

17. 2. The method for reusing a positive electrode active material according to claim 1, further comprising the steps of: mixing the washed active material with a lithium precursor solution and spray drying the solution after the washing step.

Citation Information

Patent Citations

  • Method for recovering leftover materials of lithium ion battery cathodes

    CN105870533A

  • Lithium battery material recovery method

    JP1994251805A

  • Method and system for recovering battery member

    JP1998241750A

  • Treating method of lithium battery

    JP2006236859A

  • Method for recovering lithium

    JP2013095951A